Permainan 3d Tentang Rambu Lalu Lintas Untuk Anak - Fibriandio Luddy Prakoso (Melek IT : Information Technology Journal, 2019)
The educational game is a game designed or created to stimulate thinking power including improving concentration and solving problems. Traffic signs of one of the road equipment tools in a particular form containing symbols, letters, numbers, sentences and combinations are used to provide warnings, restrictions, instructions and directions to road users. Many road users themselves do not know the meaning and meaning of traffic signs. Currently, the number of traffic violations is increasingly being carried out by the community. If the traffic violation is still allowed, then the child as the successor of the nation is feared to imitate the violation. Therefore, the authors are interested in making educational games as a medium of learning for children using 3D animation so that children can play while learning to know and understand about traffic signs.